Turbulence effects on the wake characteristics and aerodynamic performance of a straight-bladed vertical axis wind turbine by wind tunnel tests and large eddy simulations. (15th August 2016) - Peng, H.Y.; Lam, H.F.
Abstract: The wake characteristics of wind turbines are of crucial importance for the optimum placement of multiple turbines. In this study, the wake development of a straight-bladed VAWT (vertical axis wind turbine) was investigated and compared in low-turbulence smooth and grid-turbulence flows. The wake fields in both flow regimes were measured with WTTs (wind tunnel tests). To further examine the flow physics, LES (large eddy simulation) was performed with a structured mesh. An algebraic wall-modeled LES capable of overcoming the Reynolds number scaling problem was used. The LES models accurately captured the velocities in both flow regimes from the WTTs. It was shown in the WTTs that the grid turbulence benefited both self-starting and wake recovery. The LES results also suggested delayed dynamic stall and greater power production in the turbulent flows. Moreover, it was revealed by the WTTs and LES that the wake exhibited great asymmetry in the horizontal direction, whereas it was approximately symmetrical against the blade mid-span plane. Further, vortex-ring structures consisting of counter-rotating vortices in the wake were discovered in both flow regimes. This kind of flow pattern was assumed to contribute to fast wake recovery. Highlights: Experimental study of turbulence effects on wake and power performance of a VAWT. Examination of turbulence impacts on the VAWT's self-starting and wake recovery. LES investigation into wake structures and loading behaviors in two flow regimes. Identification of vortex-ring structures containing counter-rotating flow motions. Analysis of turbulence influences on wake asymmetry and discussion of the causes.